Cleaner production of iron by using waste macadamia biomass as a carbon resource. (1st August 2017) - Kumar, Uttam; Maroufi, Samane; Rajarao, Ravindra; Mayyas, Mohannad; Mansuri, Irshad; Joshi, Rakesh K.; Sahajwalla, Veena
Abstract: Macadamia nut shell, an Australian waste biomass, was pyrolyzed to produce biochars at temperatures ranging from 500 °C to 1300 °C, using lab scale horizontal tube furnace. Biochar characterization was carried out to assess their potential usefulness as a carbonaceous material in ironmaking. Thermal decomposition analysis on waste macadamia biomass was performed using thermogravimetry and kinetic studies. The changes in chemical nature and composition of produced biochars were studied using various analytical techniques. Biochar prepared at 1300 °C was found to have around 92% carbon content as well as highly ordered graphitic structure. Biochar was used as a carbon source to reduce iron oxides to metallic iron at different temperatures i.e.1000 °C, 1100 °C, 1200 °C and 1300 °C. X-ray diffraction and scanning electron microscope analysis were performed on the reduced samples to investigate the phases present in the samples and for morphology respectively. The results of the study suggest that the biochar derived from macadamia nut shell biomass waste can be used as a valuable and renewable carbon resource in sustainable and cleaner production of iron. Highlights: A novel approach to reduce iron oxide by using macadamia shell biomass waste. Less ash, high char yield, high carbon content makes char an ideal carbon source. Higher degree of reduction of iron oxide by using macshell char was observed. This sustainable approach reduces the dependency on non-renewable fossil resources.